1957
DOI: 10.1002/ar.1091280408
|View full text |Cite
|
Sign up to set email alerts
|

Length of gestation in the guinea pig with data on the frequency and time of abortion and stillbirth

Abstract: The value of the guinea pig for investigations of teratogenesis and pregnancy is enhanced by its relatively long gestation. This species-characteristic provides especial opportunity to study deleterious factors which act differentially with respect to the phases of pregnancy as do many noxious factors in man (Taussig, '36). Not until the present, however, have sufficient data been available for a statistical analysis of the temporal aspects of pregnancy, both normal and abnormal. The uncertainty which has exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1963
1963
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…For example, Goy, Hoar & Young (1957) showed that in a pure-bred strain of guinea-pigs the mean gestation length was 69-9 days for a litter size of one, whereas it was 65-3 days for a litter size of six. The litera¬ ture on this phenomenon in domestic animals is reviewed by Clegg (1959), who cites evidence for its occurrence in cattle, sheep, goats and rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Goy, Hoar & Young (1957) showed that in a pure-bred strain of guinea-pigs the mean gestation length was 69-9 days for a litter size of one, whereas it was 65-3 days for a litter size of six. The litera¬ ture on this phenomenon in domestic animals is reviewed by Clegg (1959), who cites evidence for its occurrence in cattle, sheep, goats and rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pigs produce large young which they bear after 65-72 days of pregnancy (Goy, Hoar & Young, 1957). Young are extremely precocial and begin to forage on normal food within the first days of life.…”
Section: Introductionmentioning
confidence: 99%
“…In guinea-pigs, the incidence of still-births and neonatal deaths has been found to increase with litter size (Haines, 1931;Goy et al, 1957). However, there was no significant effect of mastectomy on litter size at delivery (3-6 + 0-20 in 16 intact; 40 + 017 in 12 mastectomized, median 4 in both) or on total weight of young (including still-born) (360 ± 23-5 g and 397 + 25-3 g, respectively).…”
Section: Pregnancy and Parturitionmentioning
confidence: 99%
“…However, there was no significant effect of mastectomy on litter size at delivery (3-6 + 0-20 in 16 intact; 40 + 017 in 12 mastectomized, median 4 in both) or on total weight of young (including still-born) (360 ± 23-5 g and 397 + 25-3 g, respectively). The incidence of still-births has also been found to be higher with gestation periods longer and shorter than 69 days (Goy et al, 1957), but there was no significant effect of mastectomy on the length of pregnancy: the gestation period in 8 intact animals in which the time of mating was known was 68-8 + 0-49 (s.e.) days compared with 67-6 ± 0-43 days in 12 mastectomized (median 68 days in both).…”
Section: Pregnancy and Parturitionmentioning
confidence: 99%